Pengaruh Tax Minimization, Foreign Ownership dan Bonus Plan terhadap Transfer Pricing - Affipa Toharo; Siti Hailatul Fikriyah (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2023)
This study aims to identify and provide empirical evidence regarding tax minimization, foreign ownership, and bonus plans for transfer pricing in raw goods companies listed on BEI for the 2017-2021 period. this type of research used is quantitative research. the number of samples in this study were 75 observational data from 15 raw goods companies which were obtained using the purposive sampling method. the data used is secondary data, namely in the form of annual financial reports obtained from the official website of  BEI and the official website of each company. the data analysis technique used is descriptive statistics and panel data regression analysis using eviews-12. the results of this study based on the simultaneous test state that tax minimization, foreign ownership and bonus plans have effect on transfer pricing. Tax minimization and bonus plan has a significant effect on transfer pricing, and foreign ownership has no significant effect on transfer pricing